Gated Communities and the Digital Polis Rethinking Subjectivity, Reality, Exclusion, and Cooperation in an Urban Future - Kim, Kon.; Chung, Heewon (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This edited collection provides an alternative discourse on cities evolving with physically and virtually networked communities-the 'digital polis'-and offers a variety of perspectives from the humanities, media studies, geography, architecture, and urban studies. As an emergent concept that encompasses research and practice, the digital polis is oriented toward a counter-mapping of the digital cityscape beyond policing and gatekeeping in physical and virtual gated communities. Considering the digital polis as offering potential for active support of socially just and politically inclusive urban circumstances in ways that mirror the Greek polis, our attention is drawn towards the interweaving of the development of digital technology, urban space, and social dynamics. The four parts of this book address the formation of technosocial subjectivity, real-and-virtual combined urbanity, the spatial dimensions of digital exclusion and inclusion, and the prospect of emancipatory andempowering digital citizens. Individual chapters cover varied topics on digital feminism, data activism, networked individualism, digital commons, real-virtual communalism, the post-family imagination, digital fortress cities, rights to the smart city, online foodscapes, and open-source urbanism across the globe. Contributors explore the following questions: what developments can be found over recent decades in both physical and virtual communities such as cyberspace, and what will our urban future be like? What is the 'digital polis' and what kinds of new subjectivity does it produce? How does digital technology, as well as its virtuality, reshape the city and our spatial awareness of it? What kinds of exclusion and cooperation are at work in communities and spaces in the digital age? Each chapter responds to these questions in its own way, navigating readers through routes toward the digital polis. Chapter "Introduction - The digital polis andits practices: Beyond gated communities" is available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Introduction - The digital polis and its practices: Beyond gated communities -- Digital polis and the 'safe' feminism: Focusing on the strategies of direct punishment and gated community -- Toward digital polis: Gendered data (in)justice and data activism in South Korea -- Subjection or subjectification: representation of 'networked individuals' in Korean web novels -- Digital polis and urban commons: Justice beyond the gated community -- Production and reproduction of space and culture in the virtual realm: Gated communities as the imaginary, intermediary and real spaces -- The ghettoised city and the affect of anxiety in Park Wan-soe's 'apartment novels' -- Spatial and digital fortressing of apartment complexes in Seoul: Two case studies -- Inclusion, exclusion, and participation in digital polis: Double-edged development of poor urban communities in alternative smart city-making -- Online-based food hubs for community health and well-being: Performance in practice and its implicationsfor urban design -- Third places: The social infrastructure of the smart city. .
Keywords: Sustainability; Digital humanities; Internet of things; Sociology, Urban; Urban economics; Architecture; Sustainability; Digital Humanities; Internet of Things; Urban Sociology; Urban Economics; Cities, Countries, Regions